Gentrification in Porto: floating city users and internationally-driven urban change - Carvalho, Luís (2019)
The heightening scale of urban tourism and the fast-growing number of “floating” city users raise new challenges to understand contemporary urban change – namely for internationally open, heritage-rich medium-sized cities. Discussing the case of Porto at a time when the contested notion of gentrification infuses local politics, we highlight the transnational drivers of this process in Portugal´s second city. While acknowledging perils and benefits, we argue that more than simply leaving a footprint to be solved with taxation, internationally-driven gentrification may endanger city diversity and identity, raising implications for urban policy and for our understanding of local development as a whole.